Plasma miR-193b-3p Is Elevated in Type 2 Diabetes and Could Impair Glucose Metabolism - Hu, Hua; Zhao, Meng; Li, Zhaoyang; Nie, Hongli; He, Jia; Chen, Zhuo; Yuan, Jing; Guo, Huan; Zhang, Xiaomin; Yang, Handong; Wu, Tangchun; He, Meian (Frontiers in Endocrinology, 2022)
Objective: To explore differentially expressed miRNAs in type 2 diabetes and their potential cellular functions. Methods: We screened plasma miRNAs by miRNA array analysis and validated them by TaqMan real-time PCR in 113 newly diagnosed, untreated type 2 diabetes cases and 113 healthy controls. Low-abundance plasma proteins encoded by miR-193b-3p target genes were explored in this study population. We further investigated the potential cellular functions of the differentially expressed miRNAs in HepG2 cells. Results: miR-193b-3p was differentially expressed in type 2 diabetes cases compared to healthy controls (fold change = 2.01, P = 0.006). Plasma levels of triosephosphate isomerase (TPI1) decreased in type 2 diabetes cases (fold change = 1.37, P = 0.002). The effect of miR-193b-3p on TPI1 was verified by transfection of miR-193b-3p into HepG2 cells. miR-193b-3p inhibited the expression of YWHAZ/14-3-3ζ in the PI3K-AKT pathway, subsequently altering the expression of FOXO1 and PCK1. After transfection, cells were incubated in glucose-free medium for another 4 h. Glucose levels in medium from cells with elevated miR-193b-3p levels were significantly higher than those in medium from negative control cells (P = 0.016). In addition, elevated miR-193b-3p reduced glucose uptake by inhibiting insulin receptor (IR) and GLUT2 expression. Conclusion: Plasma miR-193b-3p levels increased in type 2 diabetes cases, and TPI1 levels decreased in both plasma and HepG2 cells with increased miR-193b-3p levels. Moreover, miR-193b-3p may affect glucose metabolism by directly targeting YWHAZ/14-3-3ζ and upregulating the transcription factor FOXO1 downstream of the PI3K-AKT pathway.